Promoting Physical Activity Through Architectural Design: Observation of Active Design Strategies in Open and Public Space - Wibowo, Andi Prasetiyo (CV. Gio Architect, 2025)
This study explores the implementation of active design principles across various architectural spaces through comprehensive photographic documentation and qualitative analysis. The research examines how built environments can promote physical activity and health through thoughtful design strategies in public spaces, open spaces, public buildings, and educational institutions. Through case studies across the United Kingdom and several European countries, the study documents and analyzes specific design features that encourage movement and physical activity. Key findings highlight the importance of accessible stairways, bicycle infrastructure, recreational areas, and well-designed open spaces in promoting active lifestyles. The research reveals that successful active design implementation depends on four core elements: ease of access and circulation, safety considerations, comfort through ergonomic design, and creative elements that engage users in physical movement. While the documented design solutions may not be directly transferable to regions with different climatic conditions, they provide valuable reference points for adaptation to local contexts. The study concludes that effective active design requires careful consideration of human behavior patterns and local cultural contexts, emphasizing the crucial role of architects, urban planners, and government bodies in developing culturally sensitive and climatically appropriate solutions.